CD8+T Cell-Related Gene Biomarkers in Macular Edema of Diabetic Retinopathy - Huang, Jing; Zhou, Qiong (Frontiers in Endocrinology, 2022)
Background: CD8+T lymphocytes have a strong pro-inflammatory effect in the tissue, some studies demonstrated that CD8+T cells are indispensable in inflammatory response of diabetic retinopathy (DR). However, the infiltration of CD8+T cells in DR, especially in diabetic macular edema (DME), and their related genes are still unclear. Methods: Download the GSE16036 dataset from the Gene Expression Omnibus (GEO) database. The abundance of 24 immune cells including CD8+T cells were evaluated by ImmuCellAI program. The differentially expressed CD8+T cell-related genes (DECD8+TRGs) between nonproliferative diabetic retinopathy (NPDR) and DME were detected by difference analysis and correlation analysis. Enrichment analysis and protein-protein interaction (PPI) network were constructed to explore the potential function of DECD8+TRGs. Lasso regression, support vector machine recursive feature elimination (SVM-RFE), Cytoscape software with related plug-ins, and Weighted Gene Co-Expression Network Analysis (WGCNA) were performed to comprehensively analyze and obtain Hub DECD8+TRGs. Hub DECD8+TRGs expression patterns were validated in other DR-related datasets. The CD8+TRG score was defined as the genetic characterization of Hub DECD8+TRGs using the GSVA sample scoring method, which can be administered to distinguish early and advanced diabetic nephropathy (DN) as well as normal and DN. Finally, the transcription levels of DECD8+TRGs in DR model mice were verified by quantitative real-time PCR (qPCR). Results: A total of 371 DECD8+TRGs were identified. 8 genes (IKZF1, PTPRC, ITGB2, ITGAX, TLR7, LYN, CD74, SPI1) were recognized as Hub DECD8+TRGs. DR and DN, which have strong clinical correlation, have been proved to be associated with CD8+T cell-related hub genes by multiple independent data sets. Hub DECD8+TRGs can not only distinguish PDR from normal and DN from normal, but also play a role in the early and progressive stages of the two diseases (NPDR vs DME, Early DN vs Advanced DN). The qPCR transcription level and trend of Hub DECD8+TRGs in DR mouse model was basically identical with human transcriptome. Conclusion: This study not only increases our understanding of the molecular mechanism of CD8+T cells in the progression of DME, but also expands people's cognitive vision of the molecular mechanism of crosstalk of CD8+T cells in the eyes and kidneys of patients with diabetes.